Study and Analysis of VoLTE Service and Its Implementation - Feng Zhou; Zhengfeng Xu; Jun Luo (Dianxin kexue)
Voice service is one of the basic services that the mobile internet carrier provides for its users. There are severa1 schemes to carry on the voice service in LTE era. The VoLTE scheme was focused on and had been studied both in theoretica1 and implementation views. Based on the 3GPP standards，the key technologies of VoLTE had been clarified，and the network architecture was also studied. Specifica11y，the interoperability between VoLTE and the 1egacy networks was analyzed to guarantee the continuity of service. Additiona11y，suggestions were given for the VoLTE development and business conducting.